Hubungan Hasil Evaluasi Pembelajaran dengan Motivasi Belajar Siswa pada Mata Pelajaran SKI di Madrasah Tsanawiyah Swasta An-Nikmah Pulau Rakyat Kabupaten Asahan - Siagian, Fauziah Azmi; Al Farabi, Mohammad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the relationship between the results of learning evaluation and students' learning motivation in Class VIII SKI Subjects at Madrasah Tsanawiyah Private An-Nikmah Pulau Rakyat, Asahan District, Academic Year 2023/2024. This type of research is descriptive correlational. The population in this study were 160 students of the An-Nikmah Private Madrasah Tsanawiyah Madrasah Tsanawiyah class, Pulau Rakyat, Asahan Regency, as many as 160 people from all 4 classes. The sample taken was 32 students. The technique of collecting data is by giving a questionnaire containing statements of motivation to learn using a Likert scale and documents of student learning outcomes in the SKI subject, the object of class VIII students at Madrasah Tsanawiyah Private An-Nikmah Pulau Rakyat, Asahan Regency. Data analysis technique uses person product moment correlation analysis and simple linear regression test. The results obtained in the person product moment correlation test were 0.592 which showed that the correlation level was at a moderate level, while the results of the simple linear regression test obtained an R square of 0.351 which showed the effect of the results of the evaluation of learning on learning motivation of 35.1%. The research instrument was tested for validity and reliability. Data analysis used the Pearson product moment correlation test and a simple regression test with the help of SPSS for window 20. Thus the results of the study showed that there was a relationship between the results of learning evaluation and learning motivation. Keywords: Learning Evaluation Results, Learning Motivation